PELATIHAN PEMBUATAN HANDICRAFT DARI LIMBAH RUMAH TANGGA ANORGANIK UNTUK MENINGKATKAN KREATIFITAS IBU-IBU DESA BLIMBINGAN - Ninda Beny Asfuri; Luncana Faridhoh Sasmito (Universitas Majalengka, 2020)
Waste of household waste becomes a problem in the environment of Blimbingan village because there are many household waste waste that accumulate and pollute the surrounding environment. Household needs products mostly plastic waste where plastic waste (inorganic) handling is relatively more complicated than organic waste, because inorganic waste can not be degradable naturally. Inorganic garbage originating from the household of Blimbingan village various such as plastic waste packaging of a household products, Kresek, aqua bottles are many of which are not utilized and only dumped in the trash. The villagers of Blimbingan, Baturan, especially mothers are less aware of the dangers posed by each day they continue to throw away their household garbage. This dedication activities aims to provide counselling and training of handicraft-value, valuable and economical value by utilizing household waste in Blimbingan village and provide guidance on how to sell to increase family income and can be a new job opportunities for the mothers of the village Blimbingan, Baturan. The methods used in this activity are by counseling, training/practice, monitoring and mentoring. Based on several series of events can be concluded that (1) of all participants carried out in the home mom Lurah in Blimbingan village is increased by 95% in terms of understanding and mastery of handicraft-like bags, flowers made, plastic bottles used for the category of good pencils. (2) teamwork and mothers are very compact and extraordinary proven to always attend training well until the event is over Keywords: Household waste, Handicraft